Posterior predicted sensitivity, specificity, PPV, NPV, covariance, and model comparison among four models with different covariance structures. - Jia Wei (120974) (2025)
Posterior predicted sensitivity, specificity, PPV, NPV, covariance, and model comparison among four models with different covariance structures.